Review: Drug Discovery and Development of Warfarin - Manao, Tirsa Ami; Asra, Ridho; Chandra, Boy (Asian Journal of Pharmaceutical Research and Development, 2022)
Background: The history of the discovery of Warfarin started from the plains of North America in Canada in 1920. Livestock in that area died from bleeding. Warfarin was first used in 1948 as a rodenticide, and in 1954 the US Food and Drug Administration (FDA) approved it for medical use as an anticoagulant. Purpose: This review article aims to discuss the history of the discovery of warfarin starting from the presence of blood clotting disorders to the point that researchers worked to find drugs that can inhibit blood clotting, namely the anticoagulant group. Research Methods: The method used is the study of relevant literature which is accessed through online sites such as Google Scholar, Research Gate, Science Direct, Springer Link, and NCBI. Conclusion: In its development, several trials such as in silico, preclinical, and clinical trials have shown significant results but are always associated with bleeding.